2016
DOI: 10.1037/gpr0000079
|View full text |Cite
|
Sign up to set email alerts
|

Competition's Role in Developing Psychological Strength and Outstanding Performance

Abstract: Competition, a topic closely associated with outstanding performance, continues to be a contentious topic ( Bonta, 1997 ; Murayama & Elliot, 2012a , 2012b ), particularly in the realm of education and schooling ( D. W. Johnson & Johnson, 1987 , 2009 ). Is competition a useful or detrimental strategy for promoting outstanding performance? Does competition contribute positively to performance or should it be avoided? In this article, we took on the challenge of exploring the relationship between competit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 95 publications
2
11
0
Order By: Relevance
“…J. 's experience is consistent with what Worrell et al (2016) describe as the psychological strength required for outstanding performance in a variety of domains, whether it is optimal performance in the athletic world, striving for kinesthetic perfection in dance, or the passion and determination of researchers to engage in scientific inquiry. Internal motivation is critical to achievement in all domains including the development of leadership talent.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…J. 's experience is consistent with what Worrell et al (2016) describe as the psychological strength required for outstanding performance in a variety of domains, whether it is optimal performance in the athletic world, striving for kinesthetic perfection in dance, or the passion and determination of researchers to engage in scientific inquiry. Internal motivation is critical to achievement in all domains including the development of leadership talent.…”
Section: Discussionsupporting
confidence: 63%
“…His early athletic success spread to other areas of his life and he appeared to thrive on reaching a goal in high-pressure situations, whether it was excelling in an algebra course, winning a state soccer championship game, or surviving intense physical training in the military. What is evident in L. J.’s experience is consistent with what Worrell et al (2016) describe as the psychological strength required for outstanding performance in a variety of domains, whether it is optimal performance in the athletic world, striving for kinesthetic perfection in dance, or the passion and determination of researchers to engage in scientific inquiry. Internal motivation is critical to achievement in all domains including the development of leadership talent.…”
Section: Discussionsupporting
confidence: 61%
“…Even with the prominent role of competition in the human experience, for both good and bad, studies of competition and competitiveness in organizations are relatively rare. In our review of the organizational science and applied psychology journals, we found only a few articles that examined competition within and between people in organizations, although we did find more research in the fields of economics (e.g., Camerer, 2011), psychology (e.g., Worrell et al, 2016), sport psychology (e.g., Gilbertson, 2016), and childhood education (e.g., Nebel, Schneider, & Rey, 2016). Given the importance of competition in organizations, there seems to be remarkably few studies on the effects of competitiveness in the workplace.…”
Section: Introductionmentioning
confidence: 90%
“…Our research coincides with other studies that have found the positive effects that constructive competition can have on teams. Constructive competition is generally found to increase performance across academic, workplace, and sports settings when competitors have a similar chance of succeeding (Worrell et al, 2016). For example, in a study examining intrateam competition amongst athletes, teams that had coaches who emphasized constructive competition during practices had better performance and greater enjoyment of athletes (Harenberg, 2014).…”
Section: Discussionmentioning
confidence: 99%